Crescimento, produção e propriedades da madeira de um clone de eucalyptus grandis x e. urophylla com enfoque energético - Santana, Wilma Michele Santos (2009)
The characterization of the potential of Eucalyptus wood as a source of raw materials must include the basis for a sustainable production biomass that is compromised with the social and economic well-being of societies. Thus, this work objective was to study the growth and yield of wood from a clone of the Eucalyptus grandis e E. urophylla as a function of dry mass, superior calorific value, carbon stocks and physical-chemical properties in order to characterize it for energy purposes. This study was also important to quantify the clonal productivity by including dendrometric variables through the adjustment of regression models. The material used in this study was 34, 48, 61, 74 and 86 months old and came from reforestation areas owned by GERDAU S.A. Based on the results obtained, it was concluded that the growth and yield of dry mass, energy production and carbon stocks can be evaluated by applying statistical models to include of dendrometric variables such as age, diameter at breast height (DBH) and Total Height. It was also verified that most of the wood characteristics analyzed were influenced by age and diameter class.